Effect of inclination angle on three-dimensional combined convective heat transfer of nanofluids in rectangular channels - Mohammed, H. A. (2013)
Combined convective nanofluids flow and heat transfer in an inclined rectangular duct is numerically investigated. Three dimensional, laminar Navier-Stokes and energy equations were solved using the finite volume method. Pure water and four types of nanofluids such as Au, CuO, SiO2 and TiO2with volume fractions range of 2% φ 7% are used. This investigation covers the following ranges: 2 × 106 Ra 2 × 107, 100 Re 1000 and 30° Θ 60°. The results revealed that the Nusselt number increased as Rayleigh number increased.SiO2nanofluid has the highest Nusselt number while Au nanofluid has the lowest Nusselt number. An increasing of the duct inclination angle decreases the heat transfer.